Low-Carbon Development : Latin American Responses to Climate Change - de la Torre, Augusto; Fajnzylber, Pablo; Nash, John (World Bank, 2012)
Climate change is already a reality. This is evidenced by the acceleration of global temperature increases, the melting of ice and snow covers, and rising sea levels. Latin America and the Caribbean region (LCR) are not exempt from these trends, as illustrated by the changes in precipitation patterns that are already being reported in the region, as well as by observations of rising temperatures, the rapid melting of Andean tropical glaciers, and an increasing number of extreme weather events. The most important force behind climate change is the rising concentration of greenhouse gases (GHGs) in the earth's atmosphere driven mainly by manmade emissions of carbon dioxide (CO2) and other greenhouse gases. Because of inertia in the climate system, the planet is likely to continue warming over the twenty-first century, and unless emissions are significantly reduced, this process could accelerate, with potentially very serious consequences for nature and mankind. There is still, however, a high degree of uncertainty regarding the specific drivers, timing, and impact of global climate change, as well as about the costs and efficacy of actions aimed at either mitigating it or dealing with its physical and economic impacts. As a result, it is very hard, at this point, to unambiguously determine economically efficient emission pathways for which the benefits of actions to mitigate climate change will exceed the costs of those actions. Despite these problems and uncertainties, there is increasing evidence suggesting that urgent action is needed in order to alter current emission trends so as to avoid reaching GHG concentration levels that could trigger large and irreversible damages. Negotiations are under way and are scheduled to be concluded in 2012 with a new agreement on a way forward. At the same time, individual countries are also considering how to respond in their own domestic policy to the challenges of climate change. LCR governments and civil society should be well informed about the potential costs and benefits of climate change and their options for decisions that will need to be made over the next decades as well as the global context in which these decisions must be taken. At the same time, the global community needs to be better informed about the unique perspective of the LCR, problems the region will face, potential contributions the region can make to combat global warming, and how to unlock the region's full potential so as to enable it to maximize its contribution while continuing to grow and reduce poverty. This report seeks to help fill both these needs.